Satisfaction with Life: Mediating Role in the Relationship between Depressive Symptoms and Coping Mechanisms - Almeida, Daniela (2021)
The purpose of this study was to analyze the mediating role of life satisfaction in the relationship between fourteen coping strategies and depressive symptoms in the Portuguese population. To undertake this work, 313 Portuguese adults aged 18 to 70 years (M = 30.73; SD = 10.79) were invited to participate in this study. Their participation was completely voluntary, and participants granted and signed informed consent previously to the filling of the validated Portuguese questionnaires. These questionnaires measured depressive symptoms, coping, and life satisfaction. The results revealed that life satisfaction displayed a mediating role in the relationship between adaptive coping mechanisms, specifically between active coping, planning, reinterpretation, and acceptance and depressive symptoms, showing a negative and significant indirect effect. Maladaptive coping mechanisms of self-blame, denial, self-distraction, disengagement, and substance use had a significant positive association with depressive symptoms, considering the mediating role of satisfaction with life. Current investigation provides initial evidence of how each coping mechanism is associated with satisfaction with life and depressive symptoms. This study clearly demonstrates that not all coping strategies are capable of influencing well-being indicators and that health professionals should focus on endorsing those that are significantly associated with lowering depressive symptoms and increasing overall satisfaction with life